Work of mathematics teacher educators : continuing the conversation - Lynch-Davis, Kathleen, 1972-; Rider, Robin L., 1963- (Monograph series (Association of Mathematics Teacher Educators) ;, 2014)
(Orginally published in 2005)A major focus of teacher education is the development of preservice teachers. However, it should not be the only focus of those who work in teacher education. Educating inservice teachers in equally important, and the conversation among those involved in mathematics teacher education needs to include discussion of this group as well. This conversation also highlights a need for professional development for teacher educators and research on the development of teacher educators. This monograph discusses issues in educating all of these groups of individuals in an effort to continue the conversation among those involded in mathematics teacher education.